Maternal Experiences with Stress Management and Caring for Children Receiving Phototherapy for Neonatal Jaundice - Klankaradi, Kuephan; Phoodanngau, Boonmee; Sirijit, Permpoon (Thai Red Cross Nursing Journal, 2023)
This descriptive qualitative study aimed to investigate the experiences of mothers in managing stress and caring for children who are receiving phototherapy for neonatal jaundice. The informants were mothers of children diagnosed with neonatal jaundice who were receiving phototherapy at the Sick Newborn Unit (SNB), a hospital in Mahasarakham province. Ten participants were recruited for the study through purposive sampling, and inclusion criteria for mothers included: 1) having a child with neonatal jaundice, 2) the child having received phototherapy for at least 24 hours, 3) being 18 years of age or older, 4) having experienced neither postpartum hemorrhage nor postpartum depression, and 5) having no prior experience in taking care of a child receiving phototherapy for neonatal jaundice. Infant criteria included 1) being a newborn with hyperbilirubinemia and receiving phototherapy for at least 24 hours, and 2) not having any health problems or congenital anomalies. Initial assessment for qualification and guidelines for a semi-structured interview were used for data collection. Data analysis utilized a combination of the content analysis methods of Chirawatkul and Erlingsson & Brysiewicz. The study revealed that the participants reflected on the experiences of being mothers of children with receiving phototherapy for neonatal jaundice. These experiences were divided into two themes: 1) Stress management, which consisted of releasing stress, trusting the doctor’s treatment, and attempting to be understanding of the child’s condition; 2) efforts to take care of the baby included efforts to increase breast milk and follow medical personnel’s advice. The research findings enhance healthcare professionals’ understanding of maternal experiences with stress management and caring for a child receiving phototherapy for neonatal jaundice. Consequently, this information can be used in developing a nursing care plan for mothers and their infants to achieve the ultimate goal of improving the quality of their lives.